1994
DOI: 10.1007/bf01222250
|View full text |Cite
|
Sign up to set email alerts
|

Hepatectomy and pylorus-preserving pancreatoduodenectomy with reconstruction of the hepatic artery, using the middle colic artery, for bile duct carcinoma: A case report

Abstract: To curatively resect advanced bile duct carcinoma which spread from the hilus to the intrapancreatic bile duct and invaded the portal vein and the hepatic artery, left hepatic lobectomy, caudate lobectomy, hepatoduodenal ligamentectomy, and pylorus-preserving pancreatoduodenectomy were performed. The hepatic artery was reconstructed by anastomosis of the middle colic artery to the right hepatic artery, and the portal vein was also reconstructed. Gastrointestinal reconstruction was performed using Traverso's pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Many reports have described hepatectomies combined with vascular resection and reconstruction for biliary malignancy [2, 4, 10, 11, 12, 13, 14, 15, 16, 17, 18], but few have described the survival effects or indications [1]. Neuhaus et al [8] and Ishiyama et al [19] reported in multivariate analyses after R0 resection that additional resection of the portal vein was the only variable with a significant influence on the survival of patients with hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have described hepatectomies combined with vascular resection and reconstruction for biliary malignancy [2, 4, 10, 11, 12, 13, 14, 15, 16, 17, 18], but few have described the survival effects or indications [1]. Neuhaus et al [8] and Ishiyama et al [19] reported in multivariate analyses after R0 resection that additional resection of the portal vein was the only variable with a significant influence on the survival of patients with hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Short segments of hepatic artery encased by tumor have been successfully resected and reconstructed by either primary anastomosis or reversed saphenous vein interposition graft (32). Another technical option is to anastomose the distal stump of the resected rRHA to the stump of the gastroduodenal artery, to the splenic artery (in an end-to-end or end-to-side fashion) using a saphenous vein jump graft (27), or to the middle colic artery (33). Another option for vein graft could be the gonadal vein (34).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Radical management, associated with vascular resection and reconstruction, in attempts to increase resectability and preserve liver parenchyma, has recently been reported, and various types of reconstruction have been performed . However, postoperative liver abscess or bilio‐enteric anastomosis leakage caused by ischemia due to arterial stenosis sometimes occur and are often fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Sekido et al7 also reported microsurgical arterial reconstruction, using the middle colic artery, in hepatectomy and pylorus‐preserving pancreatoduodenectomy for bile duct carcinoma. Although obstruction of the anastomosis was found on the arteriogram 2 months after surgery, the patient recovered, as there was a blood supply through rapidly formed collateral vessels.…”
Section: Discussionmentioning
confidence: 99%